On exact special solutions of integrable nonlinear dispersive equation - İnç, Mustafa; Bektas, Mehmet (Pergamon-Elsevier Science Ltd, 2009)
In this paper, we obtained integrable evolution equation from binormal motions of curves in the 3-dimensional Euclidean space tau(b) = (tau(m))(sss) - (tau(m+2))(s) + (tau(m))(s). Afterwards, this equation is solved by sine-cosine method and compacton solutions are obtained. As a result, abundant new compactons solitons with the absence of infinite wings, solitary pattern solutions having infinite slopes or cups, solitary wave and periodic wave solutions are obtained. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: F-Expansion Method; Solitons; Curves; Compactons; Variants; Surfaces; Motion; Kdv